Inayatullah, Suhail. “Exploring the Future of the Ummah: A Review of Emulation Models and Prefaces for the Study of Alternative Futures,” Year 5, Issue 17 (Summer 1420 AH/ 1999 CE), Pp. 43-88. - عناية الله, سهيل (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1999)
Future studies have grown in recent times and became closely linked to the planning of political institutions and governmental planning offices. Suhail Inayatullah’s article critiques the methods of approaching the future, and examines the models of future scenarios of the Muslim world. His research covers various international models, such as “the Club of Rome” model of “Limits of Growth,” the “Mankind at the Turning Point” model and “The World in 2000” model, among others. Based on the theory of post-structuralism, his research questions: what these epistemological models lack, what makes their epistemological analysis unique, and what epistemological frameworks stressed by these models there are. His research also addresses the epistemological and civilizational frameworks especially from an Islamic perspective. He concludes with some recommendations to make the Ummah more oriented towards the future.